The Western Arctic Seas encyclopedia - Zonn, I. S.; Kostianoy, A. G.; Semenov, Aleksandr V. (Professor) (Encyclopedia of seas (Springer (Firm)), 2017)
This Encyclopedia is designed to accumulate and systematize our knowledge about the unique natural water areas - the Barents, White and Kara seas, their wealth, the events that took place on its waters and shores, and the remarkable people whose lives were and are closely intertwined with the seas. The Encyclopedia contains about 900 terms and concepts related to the seas. It describes geographical features: rivers, lakes, straits, bays; provides information about towns, seaports, transport communications, basic aquatic biological species, nature reserves, national and international programs for the study of the sea, research institutes, historical monuments, activities of prominent explorers and travelers, researchers and scientists. The Encyclopedia includes a chronology of major historical events connected with the Western Arctic seas for more than 1200 years.- Resumé vydavatel